Catálogo digital de las Rutas Turísticas visitadas por los Estudiantes de la Carrera de Ecoturismo. - Cevallos Bosquez, Tania Valeria (2019)
The virtual promotion of whatever type of service or product that is required to present the public or clients has presented a very important tool in last years. The development of the present investigation Project consists on creating a digital catalog of the touristic routes visited by the students of the ecotourism career that can be beneficial for students, tourists and all who visit the catalog because it has been based on the current problem that lives tourism in our country which is the saturation of the traditional touristic routes due to the diffusion carried out during the previous government of the attractive icons which brought overloading in the same. First, I star with the diagnostic of the existent touristic routes and the touristic demand in last year according of different periods or festivities that took place in the country using bibliographical sources as Ecuador in quantity. As a result of that I did a registration of the all touristic attractions visited during the academic excursions of each level of the ecotourism career and it was carried out through a technical file card filled INSITU and pictures of the academic excursions and then I did a characterization of the touristic attractions according to the visited routes, finally, I carried out the design for each page of the digital catalog to load in a developed program made for that purpose named FLISPNACK. For that reason, it was very important the registration of all the touristic attractions according to the different visited routes of each level because I could obtain important information of the three visited regions as a result of that I can determine that exists alternative routes besides the traditional ones, it is an important contribution for the different forms of promotions that has the MINTUR. I recommend monitoring the present digital catalog through updating the information of the touristic attractions that will be visited in other levels to take advantage of the digital tools to promote them